Morphogenesis of the Ciliature During Sexual Process of Conjugation in the Ciliated Protist Euplotes raikovi - Asghar, Usman; Chi, Yong; Gao, Yunyi; Lu, Borong; Jiang, Yaohan; Gong, Ruitao; Ma, Honggang; Al-Rasheid, Khaled A. S.; Gao, Feng (Frontiers in Marine Science, 2021)
Morphogenesis is an important process that widely occurs in almost all the organisms, including the ciliated protists. Ciliates are a large group of single-celled eukaryotes that can reproduce asexually (e.g. binary fission) and perform sexual process (e.g. conjugation). Morphogenesis happens in both asexual reproduction and sexual process in ciliates and the reorganization during conjugation is more complex. However, studies of morphogenesis focusing on conjugation are very limited. Here we studied the morphogenetic process during conjugation in the marine species Euplotes raikovi Agamaliev, 1966. The results indicate that: 1) the ciliature in the ventral side reorganize twice during sexual process, i.e., conjugational and postconjugational reorganization; 2) the adoral zone of membranelles (AZM) is generated de novo in a pouch beneath the cortex during both reorganizations, with the anterior part generated during the first reorganization, while the posterior part formed during the second reorganization; 3) the frontoventral-transverse (FVT) cirri anlagen are formed de novo in both processes with the fragmentation pattern of 2:2:3:3:2; 4) one left marginal cirrus is generated de novo during both reorganizations; 5) the dorsal ciliatures remain intact during the whole process, except that the two caudal cirri originate from the end of the right-most two dorsal kineties during both reorganizations. Comparison of the morphogenetic process during conjugation demonstrate a considerably stable pattern within Euplotes while the patterns vary dramatically among different ciliates groups.